2007
DOI: 10.1002/anie.200604077
|View full text |Cite
|
Sign up to set email alerts
|

closo‐[B21H18]: A Face‐Fused Diicosahedral Borate Ion

Abstract: Siamese borates: Syntheses are described for salts of the closo‐[B21H18]− and fac‐[B20H18]2− ions. The [B21H18]− ion is the first example of a singly charged closo‐borate ion in which two icosahedral fragments are fused together such that they have a common face. The synthesis of novel weakly coordinating anions based on these frameworks is thus within reach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 37 publications
2
40
0
2
Order By: Relevance
“…X-ray crystallography confirmed that crystal parameters of obtained single crystals of 2c coincide with those of complex {Ag 2 (Ph 3 P) 6 [iso-B 20 H 18 ]} reported in Ref. [26][27][28];a nd their relative energies estimated with B3LYP/6-311 ++G(d,p). [26][27][28];a nd their relative energies estimated with B3LYP/6-311 ++G(d,p).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…X-ray crystallography confirmed that crystal parameters of obtained single crystals of 2c coincide with those of complex {Ag 2 (Ph 3 P) 6 [iso-B 20 H 18 ]} reported in Ref. [26][27][28];a nd their relative energies estimated with B3LYP/6-311 ++G(d,p). [26][27][28];a nd their relative energies estimated with B3LYP/6-311 ++G(d,p).…”
Section: Resultssupporting
confidence: 80%
“…[28] that was obtained in the course of single-crystal-to-single-crystal photocontrolled isomerism under UV radiation of crystal 1c,o rs yn-Scheme1.Isomerization reactionso fknown [B 20 H 18 ] 2À isomers as described at refs. [27] Scheme2.Synthesis of complexes 1c-1e, 2c.C onditions: i)[HNEt 3 ] 2 [trans-B 20 H 18 ]( 1equiv), AgNO 3 (2 equiv), PPh 3 (4 or 6equiv),D MF or [Ag(Ph 3 P) 3 11 BNMR spectra,n os ignals corresponding to the iso-form of the boron clusterw ere detected after 3m onths of their standing in air.I ti sc lear that presence of silver(I) and Ph 3 Pi sn eeded for preparation and isolation of the iso-form of the macropolyhedron. [27] Scheme2.Synthesis of complexes 1c-1e, 2c.C onditions: i)[HNEt 3 ] 2 [trans-B 20 H 18 ]( 1equiv), AgNO 3 (2 equiv), PPh 3 (4 or 6equiv),D MF or [Ag(Ph 3 P) 3 11 BNMR spectra,n os ignals corresponding to the iso-form of the boron clusterw ere detected after 3m onths of their standing in air.I ti sc lear that presence of silver(I) and Ph 3 Pi sn eeded for preparation and isolation of the iso-form of the macropolyhedron.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to mention that (also due to its complicated synthesis 3 ) no parent macropolyhedral borate has been found to interact with any organic molecule. We have therefore undertaken investigations aimed at testing the possibilities of the mutual interaction of purely organic and purely inorganic systems in the gas phase, the inorganic species being a unique joint-icosahedral boron hydride.…”
Section: Introductionmentioning
confidence: 99%